Integração de métodos geofísicos na modelagem crustal da Bacia de Santos - De Mio, Eduardo; Chang, Hung Kiang [UNESP]; Corrêa, Fernando Santos [UNESP] (My University, 2005)
The Santos Basin is a passive margin basin generated during the Neocominian, associated with Gondwana breakup event. The thickness of the sedimentary package reaches 15 km, including rift sequence deposited over thinned crust which originally was 35 km thick. Crustal modeling was performed over 8 lines aiming to recognize the rift phase geometry and estimate the amount of crustal stretching. The database used was: four depth converted seismic horizons, magnetic and gravimetric grids and depth to magnetic basement data. Pronounced crustal stretching has been recognized in the basin (crustal stretching factors ranging from 1.2 to 3.1), evidencing large deformation accommodation. The modeling results demand thick and widespreading volcanic layers to fit the model. These wedge shaped volcanic fill, bordered with normal faults, are a common feature in rift basins. Modeling results were confronted with depth to magnetic basement data, previously obtained, exhibiting strong correlation, mostly in shallow areas. © 2005 Sociedade Brasileira de Geofísica.
Integration of the geophysical methods in crustal modeling of the Santos basin
Keywords: Crustal modeling; Crustal stretching; Santos Basin